2005
DOI: 10.1097/01.coc.0000184682.51193.00
|View full text |Cite
|
Sign up to set email alerts
|

Erlotinib and Chemoradiation Followed by Maintenance Erlotinib for Locally Advanced Pancreatic Cancer

Abstract: The maximum tolerated dose of erlotinib with gemcitabine, paclitaxel and concurrent radiation is 50 mg/d for patients with locally advanced pancreatic cancer. Full dose maintenance erlotinib is well tolerated. Promising preliminary activity and overall survival were demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 19 publications
(28 reference statements)
0
28
0
1
Order By: Relevance
“…In a phase III trial for patients with advanced pancreatic cancer, erlotinib plus gemcitabine has shown a statistically significant survival benefit compared with gemcitabine alone (Tang et al, 2006). In another study combining erlotinib with gemcitabine and irradiation for locally advanced unresectable pancreatic cancer, most of the evaluable patients showed disease stabilization (Iannitti et al, 2005). When combined with capecitabine, erlotinib has shown considerable anti-tumor activity and better tumor control in a phase II trial for advanced pancreatic cancer.…”
Section: New Strategies For the Treatment Of Pancreatic Cancers Targementioning
confidence: 99%
“…In a phase III trial for patients with advanced pancreatic cancer, erlotinib plus gemcitabine has shown a statistically significant survival benefit compared with gemcitabine alone (Tang et al, 2006). In another study combining erlotinib with gemcitabine and irradiation for locally advanced unresectable pancreatic cancer, most of the evaluable patients showed disease stabilization (Iannitti et al, 2005). When combined with capecitabine, erlotinib has shown considerable anti-tumor activity and better tumor control in a phase II trial for advanced pancreatic cancer.…”
Section: New Strategies For the Treatment Of Pancreatic Cancers Targementioning
confidence: 99%
“…Erlotinib has been evaluated in two phase I studies using a multimodal chemoradiation approach. One study examined erlotinib plus gemcitabine and paclitaxel plus radiation followed by maintenance with erlotinib and reported a partial response rate of 46 % and median survival time of 14 months (Iannitti et al 2005). These results are supported by the other trial of erlotinib plus gemcitabine and radiation for patients with locally advanced, unresectable pancreatic cancer (Duffy et al 2008).…”
Section: Pancreatic Adenocarcinomamentioning
confidence: 90%
“…During chemoradiotherapy, at doses of ≥75 mg of erlotinib, dose-limiting toxicities (DLTs) reported were diarrhoea, dehydration, rash and small bowel stricture. The maintenance dose of 150mg was well tolerated [86].…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 95%